Influence of Roman private law on the basic principles of singular succession in the inheritance law of Ukraine, Poland and Lithuania - Цибульська, Ольга Юріївна; Цибульська, О. Ю.; Цибульская, Ольга Юрьевна; Tsybulska, Olha Yu.; Вороніна, Надія Вікторівна; Вороніна, Н. В.; Воронина, Надежда Викторовна; Voronina, Nadiia V.; Фомічова, Наталія Василівна; Фомічова, Н. В.; Фомичева, Наталия Васильевна; Fomichova, Nataliia V.; et al. (Editorial Primmate S. A. S., 2019)
The authors of the article analyzed the hereditary laws of the present day based on the designs that were used during the time of ancient Rome. The object of the study of the article is the succession – universal and singular. Universal succession is characterized by the fact that civil rights and responsibilities pass directly to other persons directly, as a whole, in full, by a single act, at the same time. Singular succession is a legal succession of individual rights or duties. By singular succession to individuals, only certain property benefits passed without any burden on them. These were the so-called testamentary disposition, carried out in the form of a legate and fideicommissum. The authors concluded that in the modern civil law of Ukraine, with the help of a legate, the testator is given the opportunity to assign the heir to the will of execution of any property obligation in favor of the person - the legatee specified by the testator. Poland and Lithuania also have a singular succession. The comparative legal analysis made by the authors testifies that they differ only in certain details from the constructions contained in the legislation of Ukraine. Thus, on the example of the analysis of the rules of inheritance law of the above-mentioned states, one can be convinced that the influence of the rules of Roman law on the corresponding testamentary constructions is present and is decisive.

Автори статті проаналізували спадкові закони сьогодення на основі задумів, які використовувалися за часів Стародавнього Риму. Об’єктом дослідження статті є спадкоємність – універсальна та одинична. Універсальне правонаступництво характеризується тим, що цивільні права та обов'язки переходять безпосередньо до інших осіб безпосередньо, в цілому, у повному обсязі, одним актом, одночасно. Сингулярне правонаступництво — це правонаступництво індивідуальних прав чи обов’язків. При одноосібному правонаступництві до фізичних осіб переходили лише окремі майнові блага без будь-якого навантаження на них. Це були так звані заповітні розпорядження, здійснювані у формі легату та фідейкомісуму. Автори дійшли висновку, що в сучасному цивільному законодавстві України за допомогою легата заповідачеві надається можливість покласти на спадкоємця за заповітом виконання будь-якого майнового зобов’язання на користь зазначеної заповідачем особи – заповідача. Польща та Литва також мають особливу спадкоємність. Зроблений авторами порівняльно-правовий аналіз свідчить, що вони лише в деяких деталях відрізняються від конструкцій, що містяться в законодавстві України. Таким чином, на прикладі аналізу норм спадкового права вищезгаданих держав можна переконатися, що вплив норм римського права на відповідні заповідальні конструкції є і є визначальним.
Tsybulska O. Influence of Roman private law on the basic principles of singular succession in the inheritance law of Ukraine, Poland and Lithuania / O. Tsybulska, N. Voronina, N. Fomichova, V. Tokareva, M. Matiiko // Amazonia Investiga. – Vol. 9. – Iss. 20. – Editorial Primmate S. A. S., 2019. – P. 144-154.
Keywords: universal succession; singular succession; legate; fideicommissum; inheritance law; testator; will; універсальне правонаступництво; єдине правонаступництво; легат; fideicommissum; спадкове право; спадкодавець; заповіт; Research Subject Categories::LAW/JURISPRUDENCE